966 Comparison of Lord and Jaboulay Procedure for Hydrocele Repair. (12th October 2021) - Henderson, L; Simpkins, S; Nalagatla, S
Abstract: Aim: Hydrocele is a common surgical pathology with a variety of operative techniques described, including Lord plication and Jaboulay procedure. Whilst current evidence suggests no difference in the recurrence rate between different techniques, the Lord's procedure is described as having the lowest complication rate. NICE guidelines state all men aged 20 - 40 should receive a pre-operative ultrasound scan. We aimed to audit the complication rate between the two procedures as well as the rate of pre-operative ultrasound assessment. Method: A retrospective review of all elective hydrocele repairs was performed within one health board over a 17-month period. All elective patients over the age of twelve and three-quarters were included, with emergency repairs excluded. Patient records were accessed, and data collected including hydrocele side and size, procedure performed, co-morbidities, medication, pre-operative ultrasound, and incidence of immediate and late complications. Results: 83 cases were identified. All men aged 20 - 40 received pre-operative ultrasound assessment. 27 (33%) repairs utilised Lord's technique, whilst 56 (67%) used Jaboulay's technique. There was no statistical difference in complication rate for all complications (10% vs. 16% p = 0.48), haematoma (3.4% vs. 12% p = 0.16), infection (1.7% vs. 12% p = 0.08) or reoccurrence (1.7% vs 0% p = 1.0) between Jaboulay's and Lord's respectfully. Conclusions: Analysis in this series showed the complication rate is higher for Lord's procedure versus Jaboulay's, however this was not found to be statistically significant. All patients aged 20-40 within our analysis received pre-operative ultrasound assessment.